Complementary impact of social capital on the adoption of productivity enhancing technologies: Evidence from Senegal - Peron A. Collins-Sowah; K. Christophe Adjin; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2019)
When a new technology is introduced to farmers, not only do individual and household factors such as risk attitudes, wealth and resource endowments affect a farm household's likelihood of technology adoption but probably more importantly, social capital structures also appear to matter. In this paper, we use the multinomial endogenous switching regression model and empirical data from a nationally representative farm household survey in Senegal to identify the causal effects of social capital on the profitability of adopting two productivity-enhancing technologies - fertilizer and improved seeds. We find a positive and significant treatment effect of social capital on total crop and household income when coupled to the adoption of productivity enhancing technologies. This suggests the need to support farmer-based organizations and improve information channels related to input and output market information, credit and insurance.
Keywords: 330; adoption; social capital; productivity enhancing technology; multinomial endogenous switching